The effect of vitamin D on the assisted reproductive techniques (ART) outcomes: A narrative review - Mitra Savabi Esfahani; Fatemeh Mokhtari; Maryam Heidari Sarvestani (Mashhad University of Medical Sciences, 2024)
Introduction: Infertility is a global health concern and the prevalence of vitamin D deficiency in the infertile population is 27% to 65%. The role of vitamin D is proposed with the expression of receptors in all types of human reproductive tissues in reproductive health and the outcomes of ART. The present study was performed with aim to investigate the effect of vitamin D on ART outcomes. Methods: In this review study, a comprehensive search was conducted in all databases of Web of Science, Scopus, Proquest, Pubmed, SID, Magiran and Google Scholar were conducted from 2015 to 2023 with English keywords of Assisted Reproductive Techniques, Vitamin D, Infertility, Male infertility, Female infertility and their Persian equivalents. Results: In total, 15 qualified articles were selected from among 1014 articles found for this study. Based on a wide range of studies, vitamin D potentially plays an important role in human fertility, and a positive correlation between high concentration of vitamin D and clinical pregnancy rate, fetal quality, and live birth rate in ART was reported. Conclusion: The effects of vitamin D on ART outcomes are controversial and its deficiency is related to ART outcomes. Probably, the effect of vitamin D deficiency on fertility is not associated with all forms of infertility and the difference in dose, time of supply and type of vitamin D may play a role in the contradiction of the results. Identifying the role of vitamin D in the pathogenesis of infertility and ART outcomes still requires further studies.